Effect of Motivation Toward Work Satisfaction Employee in Regional General Hospital East OKU - Anton Isni Sanjaya (Komunitas Dosen Indonesia, 2019)
The workforce in an organization is one of the factors that has a great responsibility towards increasing development and economic development. When training is directed and organized by a leader on an ongoing basis. With training provided to employees based on high responsibility and discipline of each employee, it will form quality human resources so that it automatically reduces the impact of the economic crisis through. The problems that exist in the General Hospital East OKU is